Methanolysis of Cottonseed Oil for Biodiesel: As Renewable Source of Energy - Ahmad, Mushtaq; Zafar, Muhammad; Ajab Khan, Mir; Hasan, Aurangzeb; Sultana, Shazia (Asian Journal of Chemistry, 2010)
In present study, cottonseed oil is chemically standardized for biodiesel as renewable source of energy. Methyl ester (biodiesel) was produced by methanolysis of cottonseed oil with methanol in the presence of NaOH as catalyst. A maximum conversion of 90 % biodiesel was achieved by methanolysis of crude cottonseed oil at 60 ºC. The viscosity of pure biodiesel, B5, B10 and B20 were 5.102, 4.051, 4.090 and 4.082, respectively and are comparable with ASTM. Other properties of the cottonseed biodiesel such as specific gravity, cetane index, flash point, pour point and cloud point are close to the high speed diesel properties. Moreover, sulphur contents of the cottonseed biodiesel are much lower than high speed diesel.